Assessment of Pharmacists Knowledge, Attitude and Practices Regarding Herbal Drug Information Services - Atavwoda, Abere Tavs (Medknow Publications & Media Pvt Ltd, 2012)
RATIONAL: Research suggests that increased consumption of herbal drugs is raising important public health concerns such as safety issues that may involve adverse effects and herb-drug interactions. The main objective of this study is to investigate the role of Pharmacists in herbal drug information dissemination. METHOD: We investigated the demographics, knowledge, attitude and practices regarding herbal drug information and regulatory laws among Pharmacists living in the six (6) States that constitute the Niger-Delta region of Nigeria. A total of 300 self-administered questionnaires were distributed to Pharmacists aged 21 years and above. FINDINGS: About half of the respondents (48.72 %) were Hospital based Pharmacists. Knowledge of herbal drugs was 46.33 % while 64 .0 % showed positive attitude towards its use. Most of the information on herbal drugs were sourced from the internet (23.08 %) while 53.48 % were aware of the laws and regulations controlling herbal drugs in Nigeria. 88.64 % were in favour of the establishment of a National Herbal Drug Research and Development Agency and 55.68 % strongly agreeing to the setting up of a Herbal Drug Information Centre. CONCLUSION: The availability of herbal drug information services will not only enhance the performance of the Pharmacists, but will also add value to the life of the patients.